PERAN PERPUSTAKAAN DALAM MENINGKATKAN MINAT BACA BAGI WARGA BINAAN DI LEMBAGA PEMASYARAKATAN KELAS III KOTAPINANG KABUPATEN LABUHANBATU SELATAN - Alyaumi Hasanah Siregar (JURNAL ILMIAH RESEARCH STUDENT, 2024)
This research discusses the role of libraries for inmates in the Class III Kotapinan Correctional Institution, South Labuan Batu District. The formulation of the problem proposed in this research is how the library program increases interest in reading among residents in the Class III Correctional Institution, Pinan City, Labuham Batu Selatan Regency and what are the supporting factors for increasing interest in reading. This research examines the library program for inmates at the Class III Correctional Institution, Pinan City, Labuan Batu Selatan District, to increase interest in reading, and what inhibiting and facilitating factors the inmates face in obtaining information. The research method used in this research is descriptive research with a qualitative approach. The data collection technique in this research is that the researcher interacts directly with the research subjects through observation, interviews and documentation. The results of the research show that the Class III library at the Pinan City Prison, South Labuan Batu District plays a role in increasing the inmates' interest in reading, and the inmates also have a significant interest in reading.